2016
DOI: 10.1016/j.ejvs.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Important Difference of the Absolute and Functional Claudication Distance in Patients with Intermittent Claudication

Abstract: The MIDs for the treadmill measured ACD and FCD can be used to interpret the clinical relevance of changes in walking distances after supervised exercise therapy and may be used in both research and individual care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…1 IC patients with aortoiliac, femoropopliteal, and multilevel stenoses showed meaningful improvements on all outcomes beyond previously established minimally important differences. [25][26][27] No between-group differences were present. These results are consistent with previous randomized trials on the effectiveness of SET, 2,28 and the presumed working mechanisms of exercise therapy in PAD.…”
Section: Discussionmentioning
confidence: 85%
“…1 IC patients with aortoiliac, femoropopliteal, and multilevel stenoses showed meaningful improvements on all outcomes beyond previously established minimally important differences. [25][26][27] No between-group differences were present. These results are consistent with previous randomized trials on the effectiveness of SET, 2,28 and the presumed working mechanisms of exercise therapy in PAD.…”
Section: Discussionmentioning
confidence: 85%
“…Another study suggested an improvement range of 1.7 to 2.2 points on the Vascular Quality of Life questionnaire as the minimum important difference in patients with intermittent claudication 1 year after revascularization. 14 A study by Van Den Houten et al 35 also reported the functional and absolute claudication distances that signify improvement as 250 m and 305 m, respectively, after 3 months of SET. 35 Gardner et al 8 estimated MCID values of 38 seconds, 95 seconds, and 152 seconds for small, moderate, and large improvements, respectively, in peak walking time.…”
Section: Discussionmentioning
confidence: 96%
“…14 A study by Van Den Houten et al 35 also reported the functional and absolute claudication distances that signify improvement as 250 m and 305 m, respectively, after 3 months of SET. 35 Gardner et al 8 estimated MCID values of 38 seconds, 95 seconds, and 152 seconds for small, moderate, and large improvements, respectively, in peak walking time. Furthermore, the 6-minute walk distance for small, moderate, and large MCID were 9 m, 24 m, and 38 m, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Although the MID represents an important threshold, of value to establish whether any observed statistical difference is of clinical relevance, 9 and important to use when designing clinical trials, 30 the MID has limitations when it comes to the assessment of individual outcomes after revascularisation. Although rare, revascularisation procedures for PAD carry a risk of severe procedure related complications 31,32 and, hence, from a patient's perspective, the achieved benefit of the procedure should be substantial.…”
Section: Discussionmentioning
confidence: 99%